Canciones de América del Sur: um estudo de orquestração - Tavernese, Alí Saboy [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The work consists in presenting orchestrations for string quintet (violin I, violin II, viola, cello and contrabass), clarinet and flute made up of songs by erudite composers from South America. The repertoire chosen is, for the most part, for soloist and the melody of the voice was not modified (in some cases there was the addition of a second voice and vocal quartet). Guyana, Suriname and French Guiana were excluded from the proposal because of the strong cultural and political ties they have with their European settlers to date, thus depriving them of typically Latin American music. The purpose of the work is to define, record and perform one of the many orchestration possibilities that emerged during the study process (the revised versions are attached). The report presents the difficulties to obtain material and, as a result, the modifications that were necessary with respect to the project, as well as the setbacks in relation to the management of people; also points out how rewarding it is to be able to stop thinking of music just like accumulation of notes by measure to begin to understand phrases, textures and musical structures. The presentation of the musical pieces showed that the work is relevant for the community in general (musicians and non musicians) because it was a novelty for the public's ears, either because they did not know the repertoire, or because a different sonority of the original piece was presented. Perhaps this was the greatest learning I take from work: to understand art always in terms of the audience.

O trabalho consiste em apresentar orquestrações elaboradas para quinteto de cordas (violino I, violino II, viola, violoncelo e contrabaixo), clarinete e flauta feitas sobre canções de compositoras e compositores eruditos de América do Sul. O repertório escolhido é, na sua maior parte, para cantor (a) solista e a melodia da voz não foi modificada (em alguns casos houve a adição de uma segunda voz e quarteto vocal). Guiana, Suriname e Guiana Francesa foram excluídos da proposta pelos fortes vínculos culturais e políticos que eles guardam, até hoje, com seus colonizadores europeus, descaracterizando assim uma música tipicamente latino-americana. O objetivo do trabalho é definir, registrar e executar publicamente uma das tantas possibilidades de orquestração que afloraram durante o processo de estudo (em anexo estão as versões revisadas). O relatório apresenta as dificuldades para obtenção de material e, em decorrência disso, as modificações que foram necessárias com relação ao projeto, bem como os contratempos em relação à gestão de pessoas; também ressalta quão gratificante é conseguir parar de pensar a música apenas como acúmulo de notas por compasso para começar a entender frases, texturas e estruturas musicais. A apresentação das obras demonstrou que o trabalho é relevante para a comunidade em geral (músicos e não músicos) pois foi uma novidade para os ouvidos do público, seja porque não conheciam o repertório, seja porque foi apresentada uma sonoridade diferente da peça original. Talvez esse foi o maior aprendizado que levo do trabalho: entender a arte sempre em função do público.
Keywords: Orquestra de câmara; Regencia (Musica); Regência de coros; Música - America Latina; Conducting